Teacher-student interaction in English classroom setting - Kurniatillah, Ratu Erlinda; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek (Politeknik Negeri Bali, 2022)
This study aimed at finding the types of teacher talk and learner talk that occur in the classroom. The research design was a descriptive qualitative method. The data source of this method was the English teachers who teach ninth-grade students of 176 Junior High School Jakarta. The data collection technique of this research was doing observation classroom and conducting an interview. The objective of this research was (1) To find out the types of teacher interaction that occur in the classroom (2) To find out the types of students interaction that occur in the classroom. This study applied observation and interviews in collecting the data. The result of the research showed the teacher-student interaction was interactive. The teacher used the teacher to talk to deliver material to the students, and students responded to the teacher. The aspect of the teacher talk employed 3 categories, and the learner employed 3 categories in the classroom interaction during the teaching-learning process. Teacher talk occurs in the classroom is lecturing, especially giving facts or opinions about content procedures and Giving their explanation. Students talk occurs in the classroom is students talk initiation specially Expressing own ideas and the interaction between teacher and students in the classroom interaction interactive they made good interaction each other.